TOWARDS SUSTAINABLE HEALTH: EXAMINING HEALTH COMMUNICATION IN RURAL VACCINATION INITIATIVES - Ippili, Tarakeswara Rao; Kurumaiah, Narumalla; Rao, Poralla Venkateshwar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health communication is an important facet of public health as it has a direct impact on the health-related behaviours of people. This paper provides a review of health communication development to assess a particular health campaign that aims at improving vaccination coverage within a rural community. The research design employed in the study is a qualitative case study feedback, which entails document analysis and semi-structured interviews to sample enriching data from multiple groups of participants from the eligible members of the community, health care providers, and personnel or coordinators of the campaign. The study aims at identifying the approaches used, the efficacy of the communication techniques used, and the consequences on the health of the community. The study reveals that a cocktail of mass awareness campaigns as well as engaging the community and digital platforms greatly enhance people’s awareness and subsequent vaccination. However, gaps including cultural beliefs, health illiteracy, and limited resources came up, pointing to the need for culturally appropriate messages and reinforcement of resources. From the case analysis, it is evident that these strategies can be effectively implemented in business operations through culturally appropriate and relevant methods.